Prawo do bezpieczeństwa i porządku publicznego w realizacji prawa do zgromadzeń. Wybrane zagadnienia - Zabłocki, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The subject of the article is the issue of security and public order, analyzed on the basis of the implementation of the constitutional right of assembly. The existing Law on Assembly contains numerous provisions on the need for security measures, both in the preparation of the assembly as well as in its course. Obligations are related both to the municipality as well as the organizer. The author makes an interpretation of selected statutory provisions with respect to the position of law and jurisprudence of the courts.
Keywords: Konstytucja Rzeczypospolitej Polskiej; prawo do zgromadzeń; wolności i prawa człowieka